The investigation of the effect of montessori approach-based stem activities on the problem-solving skills of pre-service preschool teachers - Çakır, Zehra; Altun Yalçın, Sema (Afyon Kocatepe Üniversitesi)
This research was conducted to determine whether there is any effect of the Montessori approach-based STEM activities on the development of the problem-solving skills of pre-service preschool teachers or not. The mixed-method was employed in the research. The sample of the research consisted of 50 pre-service teachers, who were taking education in the Preschool Teacher Training Department of the Faculty of Education. A single grouped pretest-posttest pattern was created to determine the difference in the problem-solving skills of the pre-service teachers in the research. The quantitative data gathered during the process of the research were analysed with the statistical methods; the qualitative data were analysed with the content analysis. The “Problem Solving Scale” and the “Semi-structured Protocol Form” were used to collect the quantitative data in the research. Qualitative data prepared to support quantitative data consists of the open-ended semi-structured protocol form. The participants were educated with the Montessori approach-based STEM education for 14 weeks. In the results reached as a result of the research, it was observed that there was a significant difference between the pre-test and post-test scores of problem-solving skills and the qualitative analysis results supported the quantitative results.

Bu araştırma, Montessori yaklaşım temelli STEM etkinliklerinin okul öncesi öğretmen adaylarının; problem çözme becerilerinin gelişimi üzerine etkisinin olup olmadığını tespit etmek amacıyla yapılmıştır. Araştırmada karma yöntem kullanılmıştır. Araştırma örneklemini 2017-2018 eğitim öğretim yılında Eğitim Fakültesi Okul Öncesi Öğretmenliği Bölümünde öğrenim gören 50 öğretmen adayı oluşturmuştur. Araştırmada öğretmen adaylarının problem çözme becerilerindeki değişimi belirlemek amacıyla tek gruplu öntest sontest deseni oluşturulmuştur. Araştırma süresince elde edilen nicel verilerin analizi istatistiksel yöntemler ile nitel verilerin analizi ise içerik analizi ile yapılmıştır. Çalışmada nicel veriler “Problem Çözme Ölçeği” ile nitel veriler ise “Yarı-Yapılandırılmış Görüşme Formu” kullanılarak toplanmıştır. Görüşme formu niceli destekleyici nitelikte ve toplamda 10 açık uçlu sorudan oluşmaktadır. Bu form çalışma sonunda sadece gönüllü 15 katılımcıya uygulanmıştır. 14 hafta boyunca adaylara Montessori yaklaşım temelli STEM eğitimleri verilmiştir. Araştırma sonucunda elde edilen bulgularda; problem çözme becerilerinin öntest ve sontest puanları arasında, anlamlı bir farklılık olduğu ve yapılan nitel analiz sonuçlarının da nicel sonuçları desteklediği gözlenmiştir. Bu bulgular ile etkinliklerin bireylerin problem çözme becerilerini geliştirdiği ve soruna farklı bakış açıları ile çözümler ürettikleri sonucuna ulaşılmıştır.
Montessori yaklaşım temelli STEM etkinliklerinin okul öncesi öğretmen adaylarının problem çözme becerilerine etkisi
Keywords: Montessori Approach; Problem-Solving; STEM